To the question of modeling of wheels and rails wear processes - Manashkin, L. A.; Myamlin, S. V. (Science and Transport Progress, 2013)
Purpose. There is a need of wear process modeling in the wheel-rail system. This is related to the fact that the wear processes in this system are absolutely different in the initial and final stages. The profile change of rail and, especially, of the wheels caused by the wear significantly affects the rolling stock dynamics, traffic safety and the resource of the wheels and rails. Wear modeling and the traffic safety evaluation requires the accounting of the low frequency component forces (including the modeling of transitional areas) affecting the wheel on the side of the rail and carriage in motion of rolling stock, so the statistical analysis is not possible. Methodology. The method of mathematical modeling of the wheel set and the rail interaction was used during the research conducting. Findings. As a result of the modeling of the wheel set motion on the rail track, the mathematic model with 19 freedom degrees was obtained. This model takes into account the axle torque and studies wheels constructions as the components of the mechanical systems, consisting of a hub and tire. Originality. The mathematic model allows evaluating the wear degree of the wheels and rails when using on the rolling stock not only all-metal wheel sets, but also compound ones with the use of spring wheels and independent rotation of semi-axes with the wheels. Practical value. The development of the improved mathematical model of freight car wheel set motion with differential rotation of the wheels and compound axles allows studying the wear processes of wheels and rails.